William Trent correspondence - Trent, William, 1715-1787?
Letter written by Trent concerning land transactions near Carlisle, Pa.
Indian trader.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Land tenure -- Pennsylvania -- Carlisle; Indian traders